Functionally Mature CD1c+ Dendritic Cells Preferentially Accumulate in the Inflammatory Arthritis Synovium - Canavan, Mary; Marzaioli, Viviana; Bhargava, Vipul; Nagpal, Sunil; Gallagher, Phil; Hurson, Conor; Mullan, Ronan; Veale, Douglas J.; Fearon, Ursula (Frontiers in Immunology, 2021)
Objective To examine the role of synovial CD1c+DCs in patients with Inflammatory Arthritis (IA) with a specific focus on the transcriptional and maturation signatures that govern their function. Methods RNA sequencing was performed on healthy control (HC) peripheral blood (PB), IA PB, and IA synovial fluid (SF) CD1c+DCs. Multiparametric flow-cytometry and SPICE analysis were used to examine site [SF and Synovial Tissue (ST) CD1c+DCs] and disease specific characteristics of CD1c+DCs, while functional assays such as antigen processing, activation, and MMP production were also performed. Results Increased frequency of CD1c+DCs (p<0.01) with a concomitant increase in CD80, CCR7 (p<0.01), and CXCR3 (p<0.05) expression was identified in IA PB compared to HC PB. Enrichment of CD1c+DCs was identified in IA synovial tissue (ST) (p<0.01) and IA SF (p<0.0001) compared to IA PB, while RNAseq revealed distinct transcriptional variation between PB and SF CD1c+DCs. Flow cytometry revealed increased expression of CD83, CD80, PD-L1, and BTLA (all p<0.05) in IA SF CD1c+DCs compared to PB, while SPICE identified synovial cells with unique co-expression patterns, expressing multiple DC maturation markers simultaneously. Functionally, synovial CD1c+DCs are hyper-responsive to TLR7/8 ligation (p<0.05), have decreased antigen processing capacity (p=0.07), and display dysregulated production of MMPs. Finally, examination of both synovial CD1c+DCs and synovial CD141+DCs revealed distinct maturation and transcriptomic profiles. Conclusion Synovial CD1c+DCs accumulate in the inflamed IA synovium in a variety of distinct poly-maturational states, distinguishing them transcriptionally and functionally from CD1c+DCs in the periphery and synovial CD141+DCs.